Formaldehyde fixation is detrimental to actin cables in glucose-depleted S. cerevisiae cells - Vasicova, Pavla; Rinnerthaler, Mark; Haskova, Danusa; Novakova, Lenka; Malcova, Ivana; Breitenbach, Michael; Hasek, Jiri (Microbial cell (Graz, Austria), 2016)
Actin filaments form cortical patches and emanating cables in fermenting cells of Saccharomyces cerevisiae. This pattern has been shown to be depolarized in glucose-depleted cells after formaldehyde fixation and staining with rhodamine-tagged phalloidin. Loss of actin cables in mother cells was remarkable. Here we extend our knowledge on actin in live glucose-depleted cells co-expressing the marker of actin patches (Abp1-RFP) with the marker of actin cables (Abp140-GFP). Glucose depletion resulted in appearance of actin patches also in mother cells. However, even after 80 min of glucose deprivation these cells showed a clear network of actin cables labeled with Abp140-GFP in contrast to previously published data. In live cells with a mitochondrial dysfunction (rho0 cells), glucose depletion resulted in almost immediate appearance of Abp140-GFP foci partially overlapping with Abp1-RFP patches in mother cells. Residual actin cables were clustered in patch-associated bundles. A similar overlapping "patchy" pattern of both actin markers was observed upon treatment of glucose-deprived rho+ cells with FCCP (the inhibitor of oxidative phosphorylation) and upon treatment with formaldehyde. While the formaldehyde-targeted process stays unknown, our results indicate that published data on yeast actin cytoskeleton obtained from glucose-depleted cells after fixation should be considered with caution.
Keywords: Abp1-RFP; yeast; Actin patches; Actin cables; Abp140-GFP